Characteristics of extracellular hydrocarbon-rich microalga Botryococcus braunii for biofuels production: Recent advances and opportunities - Jin, Jian; Dupré, Catherine; Yoneda, Kohei; Watanabe, Makoto M.; Legrand, Jack; Grizeau, Dominique (Process biochemistry (1991), 2016)
•Characteristics of Botryococcus braunii reviewed in relation to its potential use as cell factory.•A critical analysis of the advances and limits of using B. braunii strains in specific hydrocarbons hyperproduction.•Extracellular matrix characteristics analyzed in relation to control of the extracellular hydrocarbon production. Bioproduction of hydrocarbons is one of the challenges facing post-peak oil production in the future. A credible option for the production of sustainable biodiesel or biojetfuels could be microalgae oils. The species Botryococcus braunii has attracted particular interest due to its ability to accumulate large amounts of long-chain hydrocarbons, according to some special characteristics, which differentiate it from other organisms, as well as plants or bacteria. Indeed, the same species includes strains producing a high chimiodiversity of hydrocarbons, strains therefore classified into four races. In addition, this photosynthetic microorganism accumulates high hydrocarbon concentrations, which are trapped in an extracellular matrix, composed of polysaccharides and polymerized hydrocarbons. However, more work is required to understand the biological processes involved in the control of extracellular hydrocarbon accumulation. Recently, despite their slow growth rates, some strains of this microalga were grown relatively efficiently as continuous cultures in controlled photobioreactors. Potential perspectives would depend on current studies focusing on ways to improve the return on investments through either a milking-like process to separate biomass from hydrocarbons production or co-valorization of the biomass residues according to biorefinery approaches to produce compounds of industrial interest, from carotenoids to squalene, and even syngas.